Die casting / Roslan Daud, Mohamad Nizam Ibrahim and Syahriman Hakim Mansor - Daud, Roslan; Ibrahim, Mohamad Nizam; Mansor, Syahriman Hakim (2000)
When we decided to start working for the final project, first thing to consider is the title of the project. We're doing some research and investigation about the engineering subject to find the must suitable and interesting things to discuss. After some study, finally we are agreed to choose a one of the attracted topic to watch now a day, the Die-Casting technology). Demand for lightweight and recyclable aluminum components has increased dramatically over the years, especially in the automotive industry. Given their advantageous features, aluminum component produce from Die-Casting method is fast becoming more popular than they are ferrous equivalents. Today, many products including oil pump, crankcase, alternator housings, cylinder heads, transmission cases, clutch housings, steering housing, wiper housing and a host of other products are made from such method.